2023
DOI: 10.1021/acs.jafc.3c00798
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress-Induced Intestinal Barrier Impairment: Current Insights into the Aspects of Oxidative Stress and Endoplasmic Reticulum Stress

Abstract: Heat stress (HS) occurs when the sensible temperature of animals exceeds their thermoregulatory capacity, a condition that exerts a detrimental impact on health and growth. The intestinal tract, as a highly sensitive organ, has been shown to respond to HS by exhibiting mucosal injury, intestinal leakage, and disturbances in the gut microbiota. Oxidative stress and endoplasmic reticulum stress (ERS) are both potential outcomes of long-term exposure to high temperatures and have been linked to apoptosis, autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 125 publications
(252 reference statements)
0
10
0
Order By: Relevance
“…Disrupted gut flora makes the gut more susceptible to stress-related damage [ 19 ]. Meanwhile, many studies have suggested that over-activation of mast cells during allergic reactions and intestinal mucosal barrier dysfunction are associated with ER stress [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Disrupted gut flora makes the gut more susceptible to stress-related damage [ 19 ]. Meanwhile, many studies have suggested that over-activation of mast cells during allergic reactions and intestinal mucosal barrier dysfunction are associated with ER stress [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The gastrointestinal system, which is notably vulnerable, undergoes mucosal injury, increased permeability, and microbiota disturbances in response to EHS. This condition is implicated in altering the gut microbiota's composition, in turn predisposing the gut to heightened stress-related damage [ 25 ]. The dysbiosis associated with EHS is linked to neurobehavioral changes, suggesting that therapeutic modulation of the gut microbiota may offer a practical strategy for clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…The endoplasmic reticulum is essential for intracellular calcium homeostasis, modification, and transport, as well as protein synthesis and folding (Kang and Jeon, 2021). The change in temperature could cause ER stress and protein misfolding (Tang et al, 2023). Heat shock proteins (HSPs) aid the folding and function of many proteins and could prevent protein misfolding (Lanneau et al, 2010).…”
Section: Discussionmentioning
confidence: 99%